Distinct neural engagement during implicit and explicit regulation of negative stimuli. (August 2020) - Fitzgerald, Jacklynn M.; Kinney, Kerry L.; Phan, K. Luan; Klumpp, Heide
Abstract: Neuroimaging research has characterized underlying neural mechanisms of attentional control and cognitive reappraisal, common implicit and explicit forms of emotion regulation, respectively. This research suggests attentional control and reappraisal may engage similar midline and lateral areas in the prefrontal cortex (PFC); however, findings are largely based on separate studies. Therefore, the extent to which mechanisms of implicit versus explicit regulation are independent or overlapping is not clear. In the current study, 49 healthy participants completed well-validated implicit and explicit regulation tasks in the form of attentional control and cognitive reappraisal during functional magnetic resonance imaging. During implicit regulation, participants identified a target letter in a string of letters superimposed on threatening faces. To manipulate attentional control, the letter string either consisted of all targets ('Threat Low' perceptual load), or was embedded among non-target letters ('Threat High' perceptual load). During cognitive reappraisal, participants were shown aversive images and instructed to use a cognitive approach to down-regulate negative affect ('Reappraise') or to naturally experience emotions without altering them ('Look-Negative'). Order of administration of tasks was counterbalanced across participants. Whole-brain results regarding frontal activity showed ventromedial PFC/rostral anterior cingulate cortex was recruited during Threat Low > Threat High. In contrast, Reappraise > Look-Negative resulted in engagement of the dorsolateral PFC, ventrolateral PFC and dorsomedial PFC. In addition, results showed no relationship between accuracy during attentional control and self-reported negative affect during cognitive reappraisal. Results indicate attentional control in the context of threat distractors and the reappraisal of negative images are supported by discrete, non-overlapping neurocircuitries. Highlights: Healthy participants completed implicit and explicit regulation tasks during fMRI. Results indicated tasks recruited non-overlapping, discrete neurocircuitries. Findings are relevant for psychiatric illnesses with difficulty in down-regulation.